The relationship between person organization fit and rural teacher retention: The mediating role of dimension of organization commitment - Yang, Huan; Hassan, Aminuddin; Wan Jaafar, Wan Munira; Aminuddin, Ain Afiqah (Ani Publishing, 2023)
Purpose: Rural teachers are the source of rural revitalization, and the retention of rural teachers is crucial for the development of rural education. This study attempts to understand the factors that influence teacher retention in China's rural schools. It examines the link between person-organizational fit, organization commitment in its various forms (affective commitment, continuous commitment, normative commitment), and retention of rural teachers. Method: The structural equation model analysis method was used in this study. The research sample included 339 rural teachers distributed in Nanchong City, Sichuan Province. The data collection instruments were the Personal Organization Fit Questionnaire (POF), Organizational Commitment Questionnaire (OCQ), and Teacher Retention Scale (TR). Descriptive data processing and hypothesis testing was carried out with SPSS and MPLUS. Result: According to the hypothesis test results, it was revealed that retention of teachers was positively correlated with person-organization fit and other commitment-related aspects, with the exception of affective commitment, which did not appear to be directly correlated with retention. Additionally, the correlation between personal-organizational fit and rural teacher retention was mediated by continuous commitment and normative commitment. Implications for Research and Practice: We recommend that education departments should pay attention to the retention rate of rural teachers, improve the fit degree between teachers and schools, and enhance the level of organizational commitment. In addition, it is also believed that attention should be paid to teachers' affective commitment to rural schools and their emotional driving force towards rural education should be strengthened.